The rose legacy eaudiobook - Heitzmann, Kristen (Diamond of the Rockies, 2015)
Driven by hope and vengeance, Carina Maria DiGratia leaves her idyllic home in Sonoma, California, for a new life in the mining town of Crystal, Colorado. Though the town has a rough element, Carina is determined that it will be the place where her dreams come true. Early on, two men vie for her trust, but neither is what he seems. Will Carina discern the truth in time to prevent tragedy? Contains mature themes.